Research and analysis of electromagnetic interference of a motor drive control system based on PMSM with SiC MOSFET for new energy electric vehicles - Zhang, Chi; Jasni, Jasronita; Mohd Radzi, Mohd Amran; Azis, Norhafiz; He, Xiangming (Frontiers in Energy Research, 2024)
The sustainable development of the 21st century faces significant challenges due to the finite reserves of fossil fuels and environmental pollution. In the context of new energy electric vehicles (NEEVs), the wide band gap semiconductor known as silicon carbide metal oxide semiconductor field effect transistor (SiC MOSFET) and the permanent magnet synchronous motor (PMSM) have emerged as advantageous sources. However, the utilization of these components gives rise to electromagnetic interference (EMI) issues, which impede the achievement of electromagnetic compatibility (EMC) standards in the motor drive control system. This paper aims to elucidate the generation mechanism, propagation path, and test infrastructure of EMI. Furthermore, it proposes a system level conducted EMI equivalent circuit model for the motor drive control system, encompassing the power battery pack, busbar cable, LISN, three phase inverter, and PMSM. Building upon this foundation, the principles for suppressing and optimizing EMI noise are discussed. The paper concludes with the validation of simulations and experimental results, which demonstrate the effectiveness of the proposed approach.